44PCorrelation of circulating tumour cells with PET-CT in metastatic breast cancer. (24th November 2019) - Koyyala, V P B; Saini, S D; Doval, D C; Mehta, A; Suryavanshi, M; Goyal, P; Maheshwari, U D; Jajodia, A; Sharma, M; Goyal, S
Abstract: Background: Circulating tumor cells (CTC) detection has proven to be an important parameter for predicting progression-free and overall survival. CTCs provide a so-called real-time liquid biopsy which gives better opportunities for selection of treatment. Methods: A prospective observational study conducted the Rajiv Gandhi Cancer Institute & Research Centre, New Delhi. 36 treatment naïve patients of metastatic breast cancer were enrolled from April 2016 and May 2018. CTCs were detected using Cellsearch system. Correlation of CTCs with patient's outcome after chemotherapy in terms of progression-free survival (PFS) and overall survival (OS) were calculated at one year. The level of CTCs in peripheral blood was measured at baseline before chemotherapy and then at 1 month and 6 months of treatment. All patients underwent PET-CT scan at 3 months and 6 months of treatment. Results: 36 patients were included in this study. The mean CTCs at baseline was 13.8 (0-48), with 75% of patients having CTC ≥5. A positive correlation with the number of sites of metastasis with the number of CTCs was noted (p < 0.001 and R = 0.886). Around 11% of the patients had a complete response (CR) after 3 months of therapy as determined by imaging with a mean number of CTCs 21 (median 17) before starting the treatment and 4.25 (median 4.5) at 1 month (P = 0.14). Similarly, partial response at 3 months, the mean CTCs significantly decreased to 6.3 from 12.9 (p = 0.001). Patients with baseline CTCs<5 had a mean PFS of 9.8 months (95% CI of 7.2 to 12.3) and patients with baseline CTCs ≥5 had a mean PFS of 8.6 months (95% CI of 7.1 to 10.1) (p = 0.37). Patients with CTCs < 5 after one month of treatment had a mean OS of 11.6 months (95% CI of 10.8 to 12.4) and patients with CTCs≥5 after one of treatment had a mean overall survival of 9.6 months (95% CI of 8.0 to 11.2) (p = 0.08). Conclusions: Our results have implications for both standard care and clinical research in developing countries. More accurate determination of treatment effectiveness early in the course of therapy might spare patient therapy-related toxicity from futile therapy, patient families from financial toxicity and allow treatment to be changed to a more effective regimen. Legal entity responsible for the study: Rajiv Gandhi Cancer Institute and Research Centre, New Delhi. Funding: Rajiv Gandhi Cancer Institute and Research Centre, New Delhi. Disclosure: All authors have declared no conflicts of interest.